Non-nested adaptive timesteps in multilevel Monte Carlo computations - Giles, MB; Lester, C; Whittle, J (Springer International Publishing, 2016)
This paper shows that it is relatively easy to incorporate adaptive timesteps into multilevel Monte Carlo simulations without violating the telescoping sum on which multilevel Monte Carlo is based. The numerical approach is presented for both SDEs and continuous-time Markov processes. Numerical experiments are given for each, with the full code available for those who are interested in seeing the implementation details.